The bounded approximation property for spaces of holomorphic mappings on infinite dimensional spaces - Caliskan, Erhan (WILEY-V C H VERLAG GMBH, 2006)
We study the bounded approximation property for spaces of holomorphic functions. We show that if U is a balanced open subset of a Frechet-Schwartz space or (DFM)-space E, then the space R(U) of holomorphic mappings on U, with the compact-open topology, has the bounded approximation property if and only if E has the bounded approximation property.
Keywords: approximation property; bounded approximation property; holomorphic mappings; germs of holomorphic functions; Mathematics